1997
DOI: 10.1139/b97-862
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopy of two trichomycetous fungi attached to the hindgut lining of pill bugs

Abstract: Two species of trichomycetous fungi, Asellaria armadillidii (Asellariales) and Parataeniella armadillidii (Eccrinales), were found attached to the hindgut lining of the pill bug, Armadillidium vulgare. In the former fungus, the thallus was composed of a basal cell bearing an apical whorl of many lateral branches. Electron micrographs in ultrathin sections showed that an electron-opaque holdfast substance surrounded the rhizoidal projections of the basal cell. The cross wall of the thallus was the typical bifur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The description of this group is based mostly on the validating description for the Zoopagales by Benjamin (1979), except that arthrospores have been added, based on Barron's (1975) Asellariales are retained in the Fungi here due to their ultrastructural characteristics (Benny & White 2001;Manier 1973;Moss 1975;Saikawa et al 1997 The name alludes to the putative synapomorphy of dikaryotic hyphae (Tehler 1988) and was applied by James et al (2006) without formal description. Kendrick (1985) and Tehler et al (2003) referred to this group as the Dikaryomycota, but the termination '-mycota' denotes the rank of phylum under the Code.…”
Section: Typus: Zoopage Drechsler 1935mentioning
confidence: 99%
“…The description of this group is based mostly on the validating description for the Zoopagales by Benjamin (1979), except that arthrospores have been added, based on Barron's (1975) Asellariales are retained in the Fungi here due to their ultrastructural characteristics (Benny & White 2001;Manier 1973;Moss 1975;Saikawa et al 1997 The name alludes to the putative synapomorphy of dikaryotic hyphae (Tehler 1988) and was applied by James et al (2006) without formal description. Kendrick (1985) and Tehler et al (2003) referred to this group as the Dikaryomycota, but the termination '-mycota' denotes the rank of phylum under the Code.…”
Section: Typus: Zoopage Drechsler 1935mentioning
confidence: 99%
“…Also, because Harpellales has been regarded as a close relative of Kickxellales (Benny and Aldrich 1975;Moss and Lichtwardt 1976;Moss and Young 1978;Saikawa et al 1997;O'Donnell et al 1998;Tanabe et al 2000;Sato 2001), Asellariales is presumed to be closely related to Kickxellales, although there has been no direct evidence to show the relationship between Kickxellales and Asellariales, largely because there are insufficient data for Asellariales (Benny 2001). The fungus we have described here might be one of the taxa that would be a missing link connecting the two orders.…”
Section: Discussionmentioning
confidence: 91%
“…Asellariales has been regarded to be phylogenetically close to Harpellales (Manier 1973;Saikawa et al 1997) based on its septal ultrastructure (Moss and Young 1978) and germination pattern of asexual spores (Lichtwardt 1973a). Also, because Harpellales has been regarded as a close relative of Kickxellales (Benny and Aldrich 1975;Moss and Lichtwardt 1976;Moss and Young 1978;Saikawa et al 1997;O'Donnell et al 1998;Tanabe et al 2000;Sato 2001), Asellariales is presumed to be closely related to Kickxellales, although there has been no direct evidence to show the relationship between Kickxellales and Asellariales, largely because there are insufficient data for Asellariales (Benny 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a bifurcate type of septum has been re ported in Harpellales (Farr and Lichtwardt 1967), Asellariales (Manier 1973, Saikawa et al 1997, Moss 1975, Kickxellales (Young 1969), Dimargaritales (Saikawa 1977, Jeffries andYoung 1979) and Mersitaciaceae (Entomophthorales) (Saikawa 1989). How ever, Porter and Smiley (1979) concluded that the Harpellales, Kickxellales and Mucorales were not closely related based on disparate RNA molecular weights.…”
Section: Introductionmentioning
confidence: 99%